Whatever happened to thrift? : why Americans don't save and what to do about it - Wilcox, Ronald T. (Yale University Press, 2008)
It is no secret that Americans save very little: every economic index confirms as much. But to solve the real mystery, we must ask the questions, "Why?" "What are the effects on our economy?" and "What can be done about it?" In this thoroughly researc.